Justiça militar e direitos humanos no Brasil: uma análise da competência para o julgamento de crimes cometidos por militares contra civis a partir dos parâmetros constitucionais e internacionais - Reis, Ulisses Levy Silvério dos (2019)
The Brazilian Military Justice, integrated to the Judicial Power by the Constitution of 1934, works in times of peace and war. The Federal Constitution of 1988 assigns to such jurisdictional branch the competence to judge military crimes defined by law. The Military Penal Code provides that crimes committed by military personnel against civilians in time of peace, regardless of their gravity, constitute matters within the military jurisdiction. However, the constitutional clauses related to the administration of justice (especially those of access to justice and prohibition of judgment by non-competent bodies), as well as the similar norms of human rights treaties approved by Brazil, challenge such attribution, since the composition of the Military Justice of the Union and of the States-Members may lead to a “corporation’s spirit” between judges and defendants. Based on this confrontation, the research will seek to answer the following problem: the jurisdiction of the Brazilian Military Justice for the adjudication of complaints involving crimes committed by the military against civilians is compatible with the international obligations assumed by the Brazilian State in the protective framework of human rights determined by the Federal Constitution of 1988? The importance of the research is revealed by the need to discuss the obligations of the State regarding the conformation of its legislation to the human rights treaties already incorporated, which holds a qualified stature in the domestic legal order. The methodology adopted was the deductive and the consultation of documentary sources (legislation, treaties, reports, sentences, etc.) was prioritized, whose analysis was contextualized from the national and foreign literature. The thesis was divided into four chapters. In the first moment, the measures taken by the Brazilian political bodies to militarize public security in the 2010 years and to publish a normative structure responsible for exempting the military agents from being submitted to the civil control for the crimes practiced by them were discussed; the following chapter contains a review of how the monitoring mechanisms of the United Nations human rights treaties understand the functioning and competence of military courts; in the third chapter, it was analysed the scope of the State’s duty to provide protection and judicial guarantees in scenarios of impunity for crimes perpetrated by the military in the treaties of the inter-American system for the protection of human rights and the interpretation presented about the issue by the Inter-American Commission and Court of Human Rights; finally, the impact of these sources of international human rights law in Brazil was examined and how they could serve as a basis for the partial reform of the jurisdictional military system. It was concluded that the coherent reading of the constitutional block formed by the Federal Constitution of 1988 and the human rights treaties in force in the domestic order demand the necessity to exclude the jurisdiction of the Military Justice for the trial of crimes committed by the military against civilians, given the high probability that such acts constitute serious violations of human rights. Such modification may be carried out by judicial or legislative means.